UJI VALIDITAS ALAT PERAGA MAGNET SEBAGAI MEDIA PEMBELAJARAN IPA FISIKA SMP - Zukri Hanafi; Hendar Sudrajat; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to test the validity of experimental devices and experimental devices with Rnd method. Validity test was conducted at the Learning Media Development Laboratory of Physics Education Study Program of Physics Education Department of PMIPA Faculty of Teacher Training and Education University of Riau. This research was conducted from April to June 2017. With 3 lecturers validator who are experts in magnetism materials and 2 junior high school teachers who are also experts in the material. Type research is Research and Development (R & D). Research and Development (R & D) is a research method used to produce a particular product, and test the effectiveness of the product by using several stages. Magnetic props consist of 8 pieces of props with the concept of magnetism in SMP materials. The data collected in this research is primary data, that is the result of the validation assessment given by the validator to the researcher The data collection technique in this research is the validation of magnetic props done by presenting some experts or experienced experts to assess new product Designed. The experimental data validation experimental data collection technique will be validated twice, where the first validation is done by giving the correction sheet to the validator, then the validator gives suggestions for the improvement of the experimental device. The second validation is done by giving the scoring sheet to some validators. Furthermore the validator will provide an assessment of the experimental device in accordance with the indicators or aspects that have been made on the assessment instrument. The results of all assessments by validators show 8 magnetic props generating values in very good categories on the likert scale and highly valid on the index (r), so it is worth using as a medium of learning in junior highKeywords: validity, magnetic, magnetic props, Rnd